Peran Dinas Pekerjaan Umum Dan Tata Ruang Kabupaten Bengkalis Dalam Keamanan Pantai (Studi Di Pantai Pambang Pesisir Desa) - wahyu wibowo; Zainal Zainal (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2020)
This research was carried out with the intention of knowing the Role of the Bengkalis Regency Public Works andSpatial Planning Service in Coastal Security at Pambang Pesisir Village Beach. Coastal Security is an effort to protect and secure coastal areas and river estuaries from damage due to erosion, abrasion, and accretion. . In its duties and functions, the Water Resources Sector controls the destructive force of water including prevention, construction, repair andmaintenance of facilities and infrastructure for controlling floods, abrasion, erosion, on rivers, beaches and lakes. The coastal area of Pambang Pesisir Village has shrunk due to coastal abrasion. The crashing of the waves is a real threat to the residents of Pambang Pesisir Village. The research objectives were to determine the Role of the Bengkalis Regency Public Works and Spatial Planning Agency in Beach Protection and to find out the obstacles - the obstacles of the Bengkalis Regency Public Works and Spatial Planning Office in Beach Protection. Therefore, in the implementation of coastal protection, the Department of Public Works and Spatial Planning, Bengkalis Regency, through Prevention,Development, Repair and Maintenance. This type of research is descriptive qualitative research. The results of the overall interview stated that the Public Works and District Spatial Planning Office in Coastal Protection was not good. However,the author suggests optimizing community involvement in coastal protection and budget efficiency for coastal protection.